2022
DOI: 10.3389/fneur.2022.788427
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Potential of Digital Technology for Better Individualized Treatment of Parkinson's Disease

Abstract: Recent years have witnessed a strongly increasing interest in digital technology within medicine (sensor devices, specific smartphone apps) and specifically also neurology. Quantitative measures derived from digital technology could provide Digital Biomarkers (DMs) enabling a quantitative and continuous monitoring of disease symptoms, also outside clinics. This includes the possibility to continuously and sensitively monitor the response to treatment, hence opening the opportunity to adapt medication pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 98 publications
0
14
0
6
Order By: Relevance
“…The present review highlights the importance of appropriate study design for the evaluation of apps against the standard of care [ 60 , 61 , 62 ]. While all non-randomized clinical studies demonstrated improved outcomes for patients using mobile apps, studies with an RCT design and high methodological quality indicated mixed findings.…”
Section: Discussionmentioning
confidence: 99%
“…The present review highlights the importance of appropriate study design for the evaluation of apps against the standard of care [ 60 , 61 , 62 ]. While all non-randomized clinical studies demonstrated improved outcomes for patients using mobile apps, studies with an RCT design and high methodological quality indicated mixed findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the near future, a set of quantitative measures derived from wearables or apps could be considered digital biomarkers of a disease, contributing to early diagnosis, stratification of subgroups and prediction of treatment outcomes 45 .…”
Section: Discussionmentioning
confidence: 99%
“…B. Parkinson hinweisen [27]. Touch-Displays können für klinische Tests wie den Tapping-Test für Parkinsonpatienten verwendet werden [27,28].…”
Section: Praktische Anwendungunclassified
“…Technische Möglichkeiten von Mobiltelefonen und tragbaren Sensoren in Kombination mit KI-Algorithmen werden noch kaum genutzt. Hier hinkt das DiGA-Verzeichnis den technischen Möglichkeiten, die in der wissenschaftlichen Literatur beschrieben sind [13,14,[26][27][28], hinterher. Ein Grund hierfür kann die teils fehlende Evidenz für klinische Nutzen der technischen Möglichkeiten sein.…”
Section: Diskussionunclassified
See 1 more Smart Citation